FEATURES OF SUCKLING BEHAVIOUR OF GAZELLA MARICA FAWNS IN SEMI-CAPTIVE CONDITIONS - Adil UZTEMUR; Abdülkadir ORMAN (Journal of Animal and Plant Sciences, 2024)
In ungulate species, adequate and balanced nutrition for newborns is crucial, and it is primarily achieved through effective suckling by their mothers. This study investigated the sucking behavior of Gazella marica fawns under semi-captive conditions. Observations were conducted using the Focal Animal Sampling Method, and in total 177 gazelles were observed in the study period. The Kruskal-Wallis test was employed to analyze the duration between long suckling bouts and total suckling duration, while the Mann-Whitney U test was used for pairwise comparisons of suckling duration, duration between short suckling bouts, and total suckling duration. Results showed a significant difference in sucking duration between twin fawns (14.1 seconds) and single fawns (16.5 seconds) (P < 0.001). Additionally, the average sucking duration was higher in May compared to other months (P < 0.001). As the fawns matured, the frequency of suckling bouts increased, with the duration between long suckling bouts reaching 321 minutes in August (P < 0.001). However, no significant differences were observed in the total suckling duration between twin and single fawns (P > 0.05). These findings indicate some differences in the suckling behavior of gazelle fawns in semi-captivity compared to those in the wild. Further research on gazelles under consistent conditions across different breeding stations is necessary to fully understand the suckling behavior of gazelle fawns.
Keywords: Gazella fawns; average suckling duration; suckling bouts; total suckling